Early Bilingual Education and Content and Language Integrated Learning Assessment in Primary Education : Assessment Beliefs, Knowledge and Practice in Portuguese State and Private Schools - Xavier, Ana (2017)
Educational provisions, such as Early Bilingual Education (EBE) and Content and Language Integrated Learning (CLIL), where curriculum content is learnt, taught and assessed through the means of an additional language, are not yet widespread in general primary and secondary education in Portugal. Knowing how to assess in such provisions, which have a dual focus on the mastering of language proficiency and content knowledge and skills, can be intricate. The first step towards building a rationale for soundly assessing language and content at early primary level in Portuguese schools needs to first understand how teachers working in EBE and CLIL education settings view assessment and what they do with it in the classroom. This article analyses the research findings of a small scale national research study conducted in Portugal in 2013/2014 on EBE and CLIL assessment beliefs, knowledge and practice on the part of teachers working in a national pilot on early bilingual education – the Bilingual Schools Project teachers (BSPT) and teachers working in similar provisions in private schools – the Non- -Bilingual Schools Project teachers (NBSPT).